The politics of competence parties, public opinion and voters - Green, Jane 1974-; Jennings, Will 1977- (Cambridge University Press, 2017)
Using decades of public opinion data from the US, UK, Australia, Germany and Canada, and distinguishing between three concepts - issue ownership, performance and generalised competence - Green and Jennings show how political parties come to gain or lose 'ownership' of issues, how they are judged on their performance in government across policy issues and how they develop a reputation for competence (or incompetence) over a period in office. Their analysis tracks the major events causing people to re-evaluate party reputations and the costs of governing which cause electorates to punish parties in power. They reveal why, when and how these movements in public opinion matter to elections. The implications are important for long-standing debates about performance and partisanship, and reveal that public opinion about party and governing competence is, to a great extent, the product of major shocks and predictable dynamics
Keywords: Political parties / Public opinion; Party affiliation; Government accountability; Public opinion / Political aspects; Partei; Öffentliche Meinung; Evaluation